T cell tolerance induced by therapeutic antibodies. - Cobbold, S (2005)
Ever since the discovery of Medawar, over 50 years ago, that immunological tolerance was an acquired phenomenon that could be manipulated in neonatal mice, the ability to induce therapeutic tolerance against autoantigens, allergens and organ grafts has been a major driving force in immunology. Within the last 20 years we have found that a brief treatment with monoclonal antibodies that block certain functional molecules on the surface of the T cell is able to reprogramme the established immune repertoire of the adult mouse, allowing indefinite acceptance of allografts or effective curing of autoimmune diseases. We are only now just beginning to define many of the regulatory mechanisms that induce and maintain the tolerant state with the aim of being able to safely and reliably apply these technologies to human clinical situations.